Systemic Antimicrobial Treatment of Chronic Osteomyelitis in Adults: A Narrative Review - Rok Besal; Peter Adamič; Bojana Beović; Lea Papst (MDPI AG, 2023)
Chronic osteomyelitis in adults is a complex condition that requires prolonged and intensive antimicrobial therapy, but evidence on optimal selection and duration of antibiotics is limited. A review of PubMed and Ovid Embase databases was conducted to identify systematic reviews, meta-analyses, retrospective and randomised controlled trials (RCTs) on antibiotic treatment outcomes in adults with chronic osteomyelitis. Three main areas of interest were investigated: short-term versus long-term antibiotic therapy, oral versus parenteral antibiotic therapy, and combination antibiotic therapy with rifampicin versus without rifampicin. A total of 36 articles were identified and findings were synthesised using a narrative review approach. The available literature suffers from limitations, including a lack of high-quality studies, inconsistent definitions, and varying inclusion/exclusion criteria among studies. Most studies are open-labelled and lack blinding. Limited high-quality evidence exists that oral therapy is non-inferior to parenteral therapy and that shorter antibiotic duration might be appropriate in low-risk patients. Studies on the impact of rifampicin are inconclusive. Further well-designed studies are needed to provide more robust evidence in these areas.